Analysis of XYZ KAP Auditors Understanding of The Implementation of Private Entity SAK (SAK EP) - Zakkiandri, Zakkiandri (Dinasti Publisher, 2025)
Abstract Private Entity Financial Accounting Standards (SAK) are prepared to meet the financial reporting needs of private entities. The implementation of Private Entity Financial Accounting Standards (SAK EP) which will be enforced in 2025 requires auditors to have a deep understanding of the standards. This study aims to analyze the level of understanding of auditors at XYZ Public Accounting Firm (KAP) towards SAK EP. The research method used is a quantitative approach using a questionnaire as a data collection instrument. The questionnaire was distributed to auditors to measure their level of knowledge about the basic concepts, principles, and application of SAK EP in the financial statement audit process. This study is expected to provide an overview of auditor readiness in facing the implementation of SAK EP and become a basis for designing more effective training programs in the future.